2009
DOI: 10.1007/s12147-009-9084-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Performances During Labor and Birth in the Midwives Model of Care

Abstract: Previous research suggests many middle-class white women attempt to maintain femininity during labor and birth. There is also evidence that women who give birth outside the medical model may engage in more gender-deviant behaviors. The current study examines women's accounts of gender performances during birth in the midwives model of care. Participants describe themselves engaging in a number of gender-deviant behaviors, without apology or overt remorse. However, participants also describe themselves engaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…The type of care that their partners received prenatally may have contributed to this. The midwifery model of care places much less emphasis on technologically derived knowledge of birth, relying more on the midwife's hands‐on skills and the mother's experiential knowledge (Carter ). For example, they typically receive fewer ultrasounds, if any.…”
Section: Masculinity and Us Homebirthmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of care that their partners received prenatally may have contributed to this. The midwifery model of care places much less emphasis on technologically derived knowledge of birth, relying more on the midwife's hands‐on skills and the mother's experiential knowledge (Carter ). For example, they typically receive fewer ultrasounds, if any.…”
Section: Masculinity and Us Homebirthmentioning
confidence: 99%
“…Others (e.g., Cheyney ; Davis‐Floyd ; Shaw and Kitzinger ) have found that women, often deliberately, use homebirth as a time to construct a transgressive femininity, asserting the strength and resilience of the female body and rejecting the need for highly technological or medicalized assistance. Of course, women may engage in both gender‐conforming and gender‐deviant behaviors during their births (Carter ) and may reinterpret hospital messages about gender to fit their own narratives (Davis‐Floyd ).…”
Section: Introductionmentioning
confidence: 99%
“…Bartky, 1990) and 'technologies of gender' (Gavey, 1992;de Lauretis, 1987;Luke, 2009). Feminists utilizing the Foucauldian concept of 'technologies of power' have examined the various techniques/discourses through which gender/ femininity are constructed in particular sites such as heterosex (Gavey, 1992(Gavey, , 2005, the negotiation of sexual violence risks (Luke, 2009), cinema (de Lauretis, 1987, normative heterosexuality (Bartky, 1990) and childbirth (Carter, 2009;Martin, 2003).…”
Section: Technologies Of Gender and Childbirthmentioning
confidence: 99%
“…Similarly, Carter (2009) found a commitment to maintaining normative femininity in American women's childbirth accounts. Many women engaged in traditionally feminine activities during labour, for example: cooking, cleaning, laundry, sewing and care-giving.…”
Section: Technologies Of Gender and Childbirthmentioning
confidence: 99%
See 1 more Smart Citation